2012
DOI: 10.4161/hv.20212
|View full text |Cite
|
Sign up to set email alerts
|

The investigational meningococcal serogroups A, C, W-135 and Y tetanus toxoid conjugate vaccine (ACWY-TT) and the seasonal influenza virus vaccine are immunogenic and well-tolerated when co-administered in adults

Abstract: Co-administration of meningococcal serogroups A, C, W-135 and Y conjugate vaccine (ACWY-TT) with seasonal influenza vaccine was investigated in a subset of adults enrolled in a larger study evaluating lot-to-lot consistency of ACWY-TT and non-inferiority to licensed tetravalent meningococcal polysaccharide vaccine (MenPS). Subjects in this sub-study were randomized (3:1:1) to receive ACWY-TT alone (ACWY-TT group) or with seasonal influenza vaccine (Coad), or licensed MenPS alone. Serum bactericidal antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 21 publications
1
36
0
1
Order By: Relevance
“…Clinical trials conducted in Europe, Asia, the Middle East and the United States have demonstrated that MenACWY-TT is immunogenic and well-tolerated in children from 12 months of age, [12][13][14][15][16] as well as in adolescents and adults. [17][18][19][20][21] Exploratory analyses in a study of US adolescents showed that a single dose of MenACWY-TT induced statistically significantly higher hSBA titers against all 4 serogroups and significantly higher percentages of subjects with hSBA titers ≥1:8 for serogroups A, W-135 and Y than the US-licensed MenACWY-DT vaccine. 18 Another study found that 15 months after vaccinating toddlers and children with MenACWY-TT, at least 92.3%, had persisting rSBA titers ≥1:8.…”
mentioning
confidence: 96%
“…Clinical trials conducted in Europe, Asia, the Middle East and the United States have demonstrated that MenACWY-TT is immunogenic and well-tolerated in children from 12 months of age, [12][13][14][15][16] as well as in adolescents and adults. [17][18][19][20][21] Exploratory analyses in a study of US adolescents showed that a single dose of MenACWY-TT induced statistically significantly higher hSBA titers against all 4 serogroups and significantly higher percentages of subjects with hSBA titers ≥1:8 for serogroups A, W-135 and Y than the US-licensed MenACWY-DT vaccine. 18 Another study found that 15 months after vaccinating toddlers and children with MenACWY-TT, at least 92.3%, had persisting rSBA titers ≥1:8.…”
mentioning
confidence: 96%
“…63 No statistically significant differences were seen in terms of vaccine response in either group. However, exploratory analysis showed lower GMTs in the co-administration group as compared to Men-ACWY-TT for serogroups A and C, but higher GMTs to serogroups A, W and Y as compared to Men-PS.…”
Section: Co-administrationmentioning
confidence: 86%
“…At the same time, the co-administration group showed antibody responses to the three influenza strains as per the predefined criteria for acceptable immune responses set by the European Medicines Agency Committee for Proprietary Medicinal Products. 63 MenACWY-TT proved to have an acceptable safety profile in adults when co-administered with the influenza vaccine. Pain and headache were the most common solicited local and general AEs respectively in all groups and grade 3 AEs were only rarely reported.…”
Section: Co-administrationmentioning
confidence: 95%
See 1 more Smart Citation
“…MenACWY-TT aşısının çocuk, adolesan, erişkin ve 55-103 yaş arası popülasyonda da immünojenik ve güvenilir olduğu yapılan çalışmalarda gösterilmiştir (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . Baxter ve ark.…”
Section: Menacwy-tt Ile Ilgili Yürütülen Antikor Sürekliliğiunclassified